2011
DOI: 10.1007/s00192-011-1553-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bowel dysfunction with sacral neuromodulation for refractory urge urinary incontinence

Abstract: Bowel dysfunction is common in women with refractory UUI. SNS improves urinary symptoms and QOL, but improvement in bowel symptoms does not translate into significant QOL changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A recent study showed improvement of bowel dysfunction in patients implanted with SNM for urinary urgency incontinence. There was significant improvement in mean urinary and bowel symptom scores, though only urinary quality of life (QOL) scores improved …”
Section: Fecal Incontinence (Fi)mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed improvement of bowel dysfunction in patients implanted with SNM for urinary urgency incontinence. There was significant improvement in mean urinary and bowel symptom scores, though only urinary quality of life (QOL) scores improved …”
Section: Fecal Incontinence (Fi)mentioning
confidence: 99%
“…Similarly, for FI, where limited therapies exist beyond pelvic‐floor therapy and modification of stool consistency, patients should be alerted that SNM therapy exists . Patients with dual bladder and bowel disorders stand to benefit with respect to both symptoms, which may direct the clinician to educate the patient about SNM almost at the first encounter. This is discussed in further detail elsewhere in this consensus statement.…”
Section: Tips For Introduction Of Snm To Patientsmentioning
confidence: 99%
“… SNS may be indicated for a patient with FI and urinary symptoms. Such patients should be discussed with a urologist . …”
Section: Consensusmentioning
confidence: 99%
“…• SNS may be indicated for a patient with FI and urinary symptoms. Such patients should be discussed with a urologist [113][114][115][116][117][118][119]. (Abstained 0, voted 22.…”
Section: Sns For Concomitant Urinary Symptomsmentioning
confidence: 99%
“…After careful evaluation of full‐text papers 27 studies were excluded: 15 studies 23–37 did not evaluate FI assessment, six manuscripts 38–43 were just protocols, five were paediatric studies, 44–48 and one trial 49 had an inappropriate study design. Finally, 328 studies were included in our review: 306 studies…”
Section: Resultsmentioning
confidence: 99%